Basophilia and Basophiliosis in Caged Hens at 18 and 77 Weeks - Cotter , Paul F. (International Journal of Poultry Science, 2017)
Objective: The goal was to determine the frequencies and cytology variation (atypia) of basophils in caged hens at 18 and 77 weeks and the relation between basophils and heterophil/lymphocyte (H/L) ratios as stress measures. Methodology: Standard Differential Counts (SDC) were obtained from Wright stained blood films. When basophils were >5% of the total white blood cell count a two-tier Basophil Differential Count (BDC) was applied. As a first-stage, basophils were divided into “Resting” or “Reactive/atypical” types. When ~25% basophils were reactive or atypical, the second tier followed. One hundred metachromatic cells (basophils) were sorted as “Resting” or dendritic, dysgranulosis, dysplastic, dwarf, lake, mesomyelocytes, metamyelocytes, net, oncosis and toxics. Results: The study-wide basophil frequencies were ~3.5% of total leukocytes at either age. Basophil numbers were unaffected by cage styles, aviary (AV) conventional (CC) or enriched (EN). However, Total White Blood Cell Counts (TWBC) indicated leukocytosis (>25 K μL–1) and leukemoid reactions (>50 K μL–1) were common. The H/L ratios ~0.2 at 18 and ~0.3 at 77 weeks were below stress levels. Ages did not affect frequency of atypia but “Lake” and “Oncosis” basophils were more common at 77 weeks. “Basophilia” describes a sample SDC with >5% basophils, if >25% are non-resting/reactive or atypical types “basophiliosis” is applied. Conclusion: Atypical basophils are common in the blood of caged hens. Both basophilia and basophiliosis are likely inflammatory stress responses associated with Poly Microbial Bacteremia (PMB) and fungemia. A basophil differential count supplements the H/L ratio stress measure.